2009
DOI: 10.1515/cclm.2009.277
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new method for the diagnosis of alterations of Lens culinaris agglutinin binding of thyroglobulin molecules in thyroid carcinoma

Abstract: Background: The measurement of serum thyroglobulin (Tg) is widely used as a marker for recurrence of thyroid carcinoma following total thyroidectomy. However, this method cannot differentiate between benign and malignant disease. We focused on the sugar chain in the Tg molecule and investigated the usefulness of Lens culinaris agglutinin (LCA)-reactive Tg ratios in sera and wash fluids obtained during fineneedle aspiration (FNA) for the detection of thyroid carcinoma. Methods: The study was performed using 203… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Moreover, in cases of thyroid carcinoma with lymph node metastasis, Lens culinaris agglutinin-reactive Tg ratios were significantly decreased compared to patients with thyroid carcinoma without metastasis. Further studies confirm usefulness of the determination of LCA-reactive Tg ratios using an enzyme-linked immunosorbent assay for distinguishing between benign and malignant lesions (Kanai et al, 2009).…”
Section: Thyroglobulinmentioning
confidence: 53%
“…Moreover, in cases of thyroid carcinoma with lymph node metastasis, Lens culinaris agglutinin-reactive Tg ratios were significantly decreased compared to patients with thyroid carcinoma without metastasis. Further studies confirm usefulness of the determination of LCA-reactive Tg ratios using an enzyme-linked immunosorbent assay for distinguishing between benign and malignant lesions (Kanai et al, 2009).…”
Section: Thyroglobulinmentioning
confidence: 53%
“…Kanai et al [ 132 ] similarly analyzed the ratios of LCA-reactive Tg to total Tg from the sera of healthy individuals and patients with thyroid cancers utilizing an enzyme-linked immunofluorescence assay (ELISA) for the detection of Tg, which has a much higher sensitivity for the detection of Tg at low serum concentrations. This study demonstrated a reduction in the LCA-reactive-to-total-Tg ratio in patients with thyroid malignancies compared to healthy controls, regardless of total Tg serum concentration.…”
Section: Glycosylationmentioning
confidence: 99%
“…Furthermore, the fucosylated α fetoprotein-L3 (AFTL3) isoform shows higher specificity in HCC diagnosis in comparison with total AFT and worsens prognosis [48]. The lectin LCA also interacts with serum thyroglobulin (Tg), a biomarker of thyroid cancer, distinguishing between noncancerous and malignant diseases [49]. Moreover, LCA and Aleuria aurantia lectin (AAL) bind to fucosylated prostate-specific antigen (PSA), a commonly employed early diagnostic marker of prostate cancer [50,51].…”
Section: Lectins As Potential Diagnostic Toolsmentioning
confidence: 99%